Evaluasi Penggunaan Obat Antidiabetik Pada Pasien Diabetes Melitus Tipe-2 di Suatu Rumah Sakit Pemerintah Kota Padang – Sumatera Barat - Dedy Almasdy; Dita Permata Sari; Suhatri Suhatri; Deswinar Darwin; Nina Kurniasih (Fakultas Farmasi Universitas Andalas, 2015)
The appropriateness of antidiabetic usege on a public hospital in Padang - West Sumatra has been studied. This study was a descriptive study, which used patient’s medical record as data resources. The appropriateness of antidiabetic usage based on criterion which was established earlier, such as the appropriateness of indication, the appropriateness of patient, the appropriateness of regiment, and the appropriateness of drug administration. Evaluation also has been done to the potential of drug interaction. The results showed that antidiabetic usage on that hospital were 100% appropriate in term of indication and drug administration. While evaluation to appropriateness of patient and drug regiment were 95.59% and 40.82% respectively.